LIVING AL-QUR’AN DALAM TRADISI RUQYAH DI PONDOK PESANTREN SYIFAUL QULUB PALANGKA RAYA - Nisa Ghina Raudhatul Janah; Munirah Munirah (STAI Asy-Syukriyyah, 2025)
The tradition of reciting ruqyah verses represents a living practice of the Qur’an within Islamic boarding schools. This practice is not only understood as a spiritual effort, but also as a means of nurturing students’ spiritual development. This study aims to examine the implementation of ruqyah verse recitation at Syifaul Qulub Islamic Boarding School in Palangka Raya and to analyze the meanings and students’ reception of this practice within the framework of Living Qur’an studies. This research employs a qualitative approach using observation and interviews with pesantren leaders and students. Data analysis is conducted through Ahmad Rafiq’s theory of Qur’anic reception. The findings reveal that the recitation of ruqyah verses is carried out regularly using selected Qur’anic verses without additional ritual practices. The students perceive this tradition as a source of inner tranquility, spiritual protection, and discipline formation. This study concludes that the ruqyah recitation tradition constitutes a form of performative reception of the Qur’an, in which Qur’anic verses are actively lived and practiced in the daily religious life of pesantren students.